PENGARUH MATERI BAHASA INDONESIA TERHADAP KETERAMPILAN BERFIKIR KRITIS MAHASISWA - Dea Rosalina Ritonga; usiono (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study intends to investigate how Indonesian language teaching resources affect the critical thinking abilities of students. Critical thinking abilities are essential skills required in today's globalized world to facilitate analytical, logistical, and creative decision-making. The approach taken for this study is a library study method. Data collection involved gathering information from multiple sources, including books, journals, and previous research. The goal of this research is to explore the experiences, perspectives, or processes that students encounter when enhancing their critical thinking skills through Indonesian language content.